Quantitative Metabarcoding Reveals the Effects of Ecological Factors and Invasive Species on Functional Diversity of Freshwater Insects - Elia Lo Parrino; Isabel Cantera; Alessia Guerrieri; Benedetta Barzaghi; Mattia Falaschi; Martina Muraro; Serena Pozzi; Raoul Manenti; Gentile Francesco Ficetola (Molecular Ecology, 2026)
Aquatic insects are the most biodiverse freshwater animals. DNA metabarcoding data are increasingly used to assess variation in insect communities, but they are rarely integrated with information on the abundance or biomass of different taxa that can provide key insights into their functional responses. Here, we combined organismal metabarcoding and biomass estimates of different clades of aquatic insects to assess how different facets of their biodiversity (taxonomic and functional diversity; species traits) are affected by multiple stressors, including invasive species, drought and variation in vegetation. In 44 waterbodies in Northern Italy, we measured environmental features (e.g., pond surface, hydroperiod, and the presence of the invasive crayfish Procambarus clarkii ) and collected insect specimens. Specimens were weighed and then used for DNA metabarcoding. The relationship between biomass of seven insect orders and their relative abundance in metabarcoding data was used to obtain quantitative estimates of taxa biomasses across communities and to extract multiple diversity measures. Different facets of biodiversity showed distinct responses to the environmental stressors. The taxonomic diversity of insect communities strongly responded to aquatic vegetation, while functional diversity was more sensitive to the invasive crayfish. Total insect biomass was negatively related to fish presence, but insects with different functional traits showed specific responses to environmental features. Our results show that integrating metabarcoding data with biomass estimates can improve our understanding of community responses to multiple stressors and highlight the importance of considering multiple measures of diversity to get a comprehensive assessment of aquatic insects' responses to environmental variation.